Geschichte der hethitischen Religion - Haas, Volkert. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1994)
Geschichte der hethitischen Religion presents the first comprehensive representation of the religious history of the Hittites, using both cuneiform and archaeological sources of the Ancient Near East, as from the beginning of the Neolithic until the end of the era of the Hittite Great Kingdom around 1150 B.C. Special attention will be paid to Ancient Near Eastern cosmologies, the Hittite Kingship and the world of the gods. The book will lead the reader from 'national' to regional divinities and from 'types' of gods, local numina, divine attributes and symbols to the cultic inventory. A fascinating insight in sacrificial practices, in myths and popular religious customs renders the reader a comprehensive overview of the Hittite festive calendar. A historical survey will give the reader the essential reference.